Strategi Pengembangan Usaha Mikro Kecil Menengah (UMKM) di Sentra Batik Bangkalan dalam Perspektif Ekonomi Islam - Anam, Khoirul; Qadariyah, Lailatul (SAFE-Network, 2024)
This research aims to develop a strategy for developing micro, small and medium enterprises at batik centers in Bangkalan from an Islamic economic perspective. The research method used is descriptive qualitative. Data collection techniques using observation, interviews and documentation. Data analysis used in this research uses the SWOT analysis technique (Strengths, Weaknesses, Opportunities and Threats). The results of the research show that alternative strategies that can be used in developing Micro, Small and Medium Batik Enterprises in Tanjung Bumi District, Bangkalan Regency after the pandemic include using the market as a distribution place, promoting batik directly, utilizing social media and marketplaces to market batik, participating craftsmen in exhibitions to promote batik with the aim of increasing sales and expanding market share, government support in the form of developing human resource training for batik makers, establishing cooperation between batik entrepreneurs and suppliers of raw materials for making batik to obtain quality raw materials and anticipate increases in raw materials. This clearly has a big impact on the welfare of the general public and business actors and based on the perspective of Islamic Economics, working and trying to get better prosperity and happiness in this world and the hereafter is one of the commands recommended in Islam as long as it does not violate the rules of Islamic law, this is in accordance with the alternative strategy used by Micro, Small and Medium Batik Business actors in Tanjung Bumi District, Bangkalan Regency because they create business strategies that are in accordance with Islamic law so that it becomes a good thing for the existence and sustainability of Micro, Small and Medium Businesses to survive. and even increase sales and can create jobs that can help many people who are having difficulty finding work when the Covid-19 pandemic hits.